Determinants Of Servqual Dimensions On Customer Satisfaction And Loyalty In Maritime Transportation And Logistics Services - Yandi Tjendana; Diah Pranitasari (Jurnal Ecoment Global, 2024)
Objective: This study aims to examine the SERVQUAL dimensions (tangibles, reliability, responsiveness, assurance, and empathy) in relation to service quality and customer loyalty. Design/Methods/Approach: This study employs a quantitative research approach. The population consists of all customers of PT. Bintang Samudera Mandiri Line's maritime transportation and logistics services, totaling 110 companies. The sampling technique used is random sampling, with a sample size of 86 respondents. Data was collected through questionnaires distributed via Google Forms. The data analysis method utilizes SmartPLS 4.0 software. Findings: Tangibles have a significant impact on customer satisfaction. Reliability also influences customer satisfaction. Similarly, responsiveness affects customer satisfaction. However, assurance and empathy do not impact customer satisfaction. Furthermore, customer satisfaction does not significantly influence customer loyalty. Tangibles, reliability, responsiveness, assurance, and empathy do not indirectly affect customer loyalty through customer satisfaction. Originality/Value: No previous studies on SERVQUAL, customer satisfaction, and loyalty have been conducted at PT. Bintang Samudera Mandiri Line. Practical/Policy implication: Companies can use the results of this study to improve their service quality, the findings of this study provide guidance for companies to focus on the service dimensions that most affect customer satisfaction. Companies can prioritize strengthening Tangibles and Reliability to achieve increased customer satisfaction and loyalty, this study also shows the importance of efficiency and reliability in the delivery process. Therefore, companies can improve their logistics infrastructure and management system to ensure on-time delivery and better management of customer complaints. Keywords: Tangibles, Reliability, Responsiveness, Assurance, Empathy, Customer Satisfaction, and Customer Loyalty